Cydonia oblonga Mill. Pulp Callus Inhibits Oxidative Stress and Inflammation in Injured Cells - Federica Gubitosa; Daniele Fraternale; Roberta De Bellis; Andrea Gorassini; Leila Benayada; Laura Chiarantini; Maria Cristina Albertini; Lucia Potenza (MDPI AG, 2023)
The pharmacological activity of a callus extract from the pulp of Cydonia oblonga Mill., also known as quince, was investigated in murine macrophage (RAW 264.7) and human keratinocyte (HaCaT) cell lines. In particular, the anti-inflammatory activity of C. oblonga Mill. pulp callus extract was assessed in lipopolysaccharides (LPS)-treated RAW 264.7 by the Griess test and in LPS-treated HaCaT human keratinocytes by examining the expression of genes involved in the inflammatory process, including nitric oxide synthase (iNOS), interleukin-6 (IL-6), interleukin-1β (IL-1β), nuclear factor-kappa-B inhibitor alfa (ikBα), and intercellular adhesion molecule (ICAM). The antioxidant activity was evaluated by quantizing the reactive oxygen species (ROS) production in the hydrogen peroxide and tert-butyl hydroperoxide-injured HaCaT cell line. The obtained results indicate that C. oblonga callus from fruit pulp extract has anti-inflammatory and antioxidant activities, suggesting its possible application in delaying and preventing acute or chronic diseases associated with aging or in the treatment of wound dressing.